Day 2 Wed, February 10, 2016 2016
DOI: 10.2118/179177-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modeling of Interwell Fracturing Interference: An Eagle Ford Shale Oil Study - Refracturing

Abstract: This paper continues the investigation of interwell fracturing interference for an infill drilling scenario synthetic case based on Eagle Ford available public data and explores pressure and stress-sink mitigation strategies applied to the simulation cases developed in the previous publication (SPE 174902). Emphasis is given to refracturing scenarios, given the intrinsic restimulation value for depleted parent wells and the strategic importance due to the current low oil prices. The stress and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…By creating the pressure barrier around the parent well, the child well's created fracture network is more likely to extend into undepleted reservoir areas with higher remaining oil in place. This occurrence has been modelled and shown by Marongio-Porcu et al (2015) and Morales et al (2016).…”
Section: Single Well Refracturing Versus Parent Well Protection Reframentioning
confidence: 56%
See 2 more Smart Citations
“…By creating the pressure barrier around the parent well, the child well's created fracture network is more likely to extend into undepleted reservoir areas with higher remaining oil in place. This occurrence has been modelled and shown by Marongio-Porcu et al (2015) and Morales et al (2016).…”
Section: Single Well Refracturing Versus Parent Well Protection Reframentioning
confidence: 56%
“…Instead, the current production rates of the well tripled. Morales et al (2016) modeled the interwell fracture interference using a complex fracture modeling workflow for an Eagle Ford study. In this study, Morales et al found that refracturing the parent well before completing the new offset wells can not only increase the production of the existing parent well, but it can also increase the production potential of the new infill wells, as shown in Fig.…”
Section: Production Results For Parent Well Protection Refracturingmentioning
confidence: 99%
See 1 more Smart Citation
“…This interwell communication can be portrayed as "pressure sinks" that interfere with induced fracture effectiveness, and might affect unconventional EOR methods efficacy if they are overridden or not accounted for. For instance, numerous documented studies have demonstrated fracture interference occurrence and assessed this phenomenon in unconventional reservoirs (Ambrose et al, 2011;Manchanda et al, 2013;Portis et al, 2013;Sardinha et al, 2014;Sani et al, 2015;Awada et al, 2016;Morales et al, 2016;Klenner et al, 2018;Seth et al, 2018;Yu and Sepehrnoori, 2018). The current interest is focused on warding off negative impacts caused by fracture hits interwell propagation and affecting further productive wells.…”
Section: Motivation Of the Studymentioning
confidence: 99%
“…As shown in Figure 11(b), the cumulative gas production of the well increases from 0.48 × 10 8 m 3 to 0.54 × 10 8 m 3 while the hydraulic fracture half-length increases from 70 m to 110 m. In addition, the reservoir pressure decreases slower with higher hydraulic fracture half-length, which is beneficial for long-time production, as shown in Figures 12 and 13. However, in refracturing, the fracture does not follow the same path of the initial fracture due to the change in stress anisotropy; it is not easy to obtain longer fracture length [14]. Figure 11: Effects of hydraulic fracture half-length on: (a) gas flow rate and (b) gas flow rate of refracturing through new perforation zones.…”
Section: Hydraulic Fracture Half-lengthmentioning
confidence: 99%